The Impact of Social Events on The Main Character in The Novel Violeta by Isabel Allende - Ali, Muhammad Ilham (EDUJ : English Education Journal, 2023)
This research aims to analyze the influence of social events on the main character in the novel "Violeta" by Isabel Allende, published in 2022. Social events, such as parties, family gatherings, and demonstrations, significantly shape characters within a narrative. By examining the protagonist's experiences and reactions to these events, this research seeks to understand their impact on the character's development and transformation. Using a qualitative approach, this research employs literary analysis methods to explore the intricate relationship between social events and the main character's journey. By delving into the novel's narrative and employing literature study techniques, the reserach aims to uncover the nuanced effects of social events on the character's psyche, motivations, and relationships. This research shows that social events significantly influence the main character's life journey. The findings of this research contribute to the broader understanding of character development in literature and shed light on the role of social events as catalysts for change. By analyzing the main character's interactions and responses to various social events, this research offers insights into how external factors influence the character's growth and shape the overall narrative. Keywords: character development; social event; sociological approach.